Outcomes of Type I Tympanoplasty using a Cartilage Shield Graft - Ghazi Ahmed, Murad; M. Said Aljaff, Said; Asaad Abdulkareem, Hiwa (Kurdistan Journal of Applied Research, 2020)
Background: Type I tympanoplasty surgery is an effective routine technic that had been used for tympanic reconstruction to improve hearing. Objectives: The aim was to measure the effect of type I tympanoplasty surgery using the cartilage shield graft (CSG) in term of graft uptake (anatomical outcome) and hearing gains (functional outcomes) of patients with poor prognostic factors. Method and Materials: In this study, 20 patients with perforation exceeded 50%, but limited to the tympanic membrane were recruited for type I tympanoplasty surgery. The study was conducted in the Otolaryngology/Head and Neck surgery training center in Sulaimani Teaching Hospital in Sulaimani city for one year period. Bellucci classi?cation was used to evaluate otorrhea risks. Results: The majority of patients were female (90%), with a mean ± SD (standard deviation) of ages of 37.15 ± 14.01 years. Most of the patients (40%) were presented with a mild hearing loss of 26-40 decibels (dB). Type I tympanoplasty surgery using the cartilage shield graft (CSG) had significantly decreased the hearing loss and air-bone gap (p-value = 0.046 and 0.006, respectively). The mean differences in hearing loss and air-bone gap were 5.05 dB and 6.75 dB, respectively. Conclusions: CSG in type I tympanoplasty surgery is an effective solution in anatomical outcome (Graft uptake) and functional outcomes (hearing gains) which had been reflected in reducing hearing loss and air-bone gap (average hearing gain of 5dB) in patients presented with tympanic membrane perforations. No improvement in the functional outcomes was observed in patients presented with severe hearing loss pre-operatively.